Trade and developing countries : Volume 50 - Morton, Kathryn; Tulloch, Peter (London : Routledge, 2013)
The book considers the conflicting views on the role of trade in development, and the range of policy choices which follow from them for developing countries. It also examines the position of developing countries in world trade at present.
Includes bibliographical references and index.
usc 25/10/17
Loans
Keywords: Commerce; Trade; Developing countries